-6x+3(x+3)=36

Simple and best practice solution for -6x+3(x+3)=36 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6x+3(x+3)=36 equation:


Simplifying
-6x + 3(x + 3) = 36

Reorder the terms:
-6x + 3(3 + x) = 36
-6x + (3 * 3 + x * 3) = 36
-6x + (9 + 3x) = 36

Reorder the terms:
9 + -6x + 3x = 36

Combine like terms: -6x + 3x = -3x
9 + -3x = 36

Solving
9 + -3x = 36

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + -3x = 36 + -9

Combine like terms: 9 + -9 = 0
0 + -3x = 36 + -9
-3x = 36 + -9

Combine like terms: 36 + -9 = 27
-3x = 27

Divide each side by '-3'.
x = -9

Simplifying
x = -9

See similar equations:

| 5x+27=4x-72 | | 6(3x-7)-3=6(x-3)+45 | | 69=-4x-5x+6 | | 5/6=x/24 | | 7n^2+7n-140= | | x/3=(x+5)/12 | | 3n+4=10 | | 8+7x+20+3x=180 | | 6x=5/24 | | r^2-23= | | 34+48= | | 37-3x=6x+24 | | b(x+a)-cx=ay-2bx | | 3x^2-29x+40= | | -x(5x-5)=0 | | -9(x+7)=5x-35 | | 9y-33=3(y+7) | | 4(x+7)=-4x+4 | | 3x+(-7)=-25 | | 8y-32=-8(y+6) | | 25x^2-45x+8= | | 5x^2-36x+36= | | 35-19=2(x-8) | | graphy=-2x-4 | | 3x^2/5=27 | | 4k^2-9= | | 1.2y=3+y+1 | | 3y=8+y+1 | | 10x^2-41x-45= | | -9x=6 | | 2v+7-5v=-17 | | 7=-3+9 |

Equations solver categories